KARAKTERISTIK ORGANOLEPTIK, FISIKOKIMIA, DAN MIKROBIOLOGI DADAR GULUNG ES TELER DENGAN SUBSTITUSI TEPUNG TALAS BENENG - Rahmayanti, Diana; Fathia, Aisha Shahrin; Rohmah, Vita Shofiyah; Haq, Dzulqornain Jihadul; Hendra, Fadhia Shafira Oktavia; Nuralifah, Balqis; Nurtiana, Winda (Leuit : Journal of Local Food Security, 2025)
S'teler roll is an innovative market snack in the form of a rolled pancake with es teler filling and substitution of beneng taro flour to increase nutritional value and utilise local food. This study aims to determine the effect of substituting beneng cassava flour on the physical, chemical, microbiological, and organoleptic characteristics of s’teler roll. Four formulations were tested (f1–f4) with beneng taro flour proportions of 20–35%. Analysis methods included organoleptic testing by 30 semi-trained panelists, chemical testing (moisture content, ash, fat, protein, starch, total sugar, and oxalic acid), physical (colour), and microbiological (alt) tests. The organoleptic results indicated that f1 (80:20) was the best formulation based on the de garmo method, with the highest scores for colour and texture parameters. Chemical analysis of f1 showed a moisture content of 62.71%, protein 2.73%, fat 4.5%, ash 0.63%, starch 16.78%, total sugar 46.73%, and oxalic acid 86.37 mg/kg. Physical analysis shows l* value of 54.21, a* 21.82, b* 6.47, and chroma 22.76, with a dominant pink colour. The alt result reached 5.9×10⁵ cfu/g, indicating the potential for microbial contamination due to fresh ingredients such as fruit and vla.